2017
DOI: 10.5194/bg-14-1541-2017
|View full text |Cite
|
Sign up to set email alerts
|

Positive Indian Ocean Dipole events prevent anoxia off the west coast of India

Abstract: Abstract. The seasonal upwelling along the west coast of India (WCI) brings nutrient-rich, oxygen-poor subsurface waters to the continental shelf, favoring very low oxygen concentrations in the surface waters during late boreal summer and fall. This yearly-recurring coastal hypoxia is more severe during some years, leading to coastal anoxia that has strong impacts on the living resources. In the present study, we analyze a 1/4 • resolution coupled physical-biogeochemical regional oceanic simulation over the 19… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 91 publications
6
47
0
Order By: Relevance
“…The leading mode of interannual SLA variability in the Indian Ocean is associated with the IOD and is very well reproduced by our model. The ST contribution is indeed weaker for negative than for positive IODs, as hypothesized by Parvathi et al (2017), but only by~20%, while the total SLA is weaker by~60%. Equatorial easterly wind anomalies typical of positive IODs extend sufficiently northward to STIP region to trigger downwelling coastal Kelvin waves, which dominate WCI SLA during late summer and fall.…”
Section: Processes Of Iod-induced Interannual Sea Level Variationsmentioning
confidence: 51%
See 4 more Smart Citations
“…The leading mode of interannual SLA variability in the Indian Ocean is associated with the IOD and is very well reproduced by our model. The ST contribution is indeed weaker for negative than for positive IODs, as hypothesized by Parvathi et al (2017), but only by~20%, while the total SLA is weaker by~60%. Equatorial easterly wind anomalies typical of positive IODs extend sufficiently northward to STIP region to trigger downwelling coastal Kelvin waves, which dominate WCI SLA during late summer and fall.…”
Section: Processes Of Iod-induced Interannual Sea Level Variationsmentioning
confidence: 51%
“…It is therefore important to understand the processes by which IOD influences the WCI. Along the same lines, Parvathi et al (2017) reported an asymmetric influence of positive and negative IOD events on WCI oxycline/thermocline variations, with positive IODs suppressing anoxia, while negative IODs having a less systematic impact. Here we use a linear ocean model to explore the main processes that influence interannual SLA (and hence thermocline/oxycline variations) along the WCI during an IOD event.…”
Section: Processes Of Iod-induced Interannual Sea Level Variationsmentioning
confidence: 68%
See 3 more Smart Citations